The Green Archipelago : Forestry in Pre-Industrial Japan - Totman, Conrad D. (Book collections on Project MUSE., 1989)
The Japanese are conscious of the lush green of their homeland, which they refer to as 'the green archipelago'. This work states that this lush verdue is not a monument to nature's benevolence and Japanese aesthetic sensibilities, but the hard-earned result of generations of human toil that converted the archipelago into one great forest preserve.